Odpowiedź :
f(x)=-x²-4x+1 dla x=3√2-2.
f(3√2-2)=-(3√2-2)²-4(3√2-2)+1 =
=-(18-12√2+4)-12√2+8+1=
=-18+12√2-4-12√2+8+1=
=-22+9=-13
f(3√2-2)=-(3√2-2)²-4(3√2-2)+1 =
=-(18-12√2+4)-12√2+8+1=
=-18+12√2-4-12√2+8+1=
=-22+9=-13
Wyznacz wartość funkcji f(x)=-x²-4x+1 dla x=3√2-2.
f(x)=-x²-4x+1
f(3√2-2)=-(3√2-2)²-4(3√2-2)+1=-(18-12√2+4)-12√2+8+1=-18+12√2-4-12√2+9=
-13
f(x)=-x²-4x+1
f(3√2-2)=-(3√2-2)²-4(3√2-2)+1=-(18-12√2+4)-12√2+8+1=-18+12√2-4-12√2+9=
-13
Wyznacz wartość funkcji f(x)=-x²-4x+1 dla x=3√2-2. =
f(3√2-2)=-(3√2-2)²-4(3√2-2)+1 = -(18-12√2+4)-12√2+8+1=
=-18+12√2-4-12√2+8+1 =-22+9=-13
f(3√2-2)=-(3√2-2)²-4(3√2-2)+1 = -(18-12√2+4)-12√2+8+1=
=-18+12√2-4-12√2+8+1 =-22+9=-13